The Effect of Prohexadione-Ca on Starch Content of Potato (Solanum tuberosum) G0 Median in Medium Plains - Dewi Hernawati; Tati Krinstanti; Edi Kusnadi (UIN Sunan Gunung Djati Bandung, 2025)
The research conducted is entitled